Facile synthesis of azobenzene-containing polyamide 6 with low melting point and good anti-dripping performance. (June 2022) - Fan, Shuo; Xiao, Yao; Huang, Jiemei; Hu, Yale; Huang, Kunlin; Zhang, Hongxia
Abstract: An inherent functional PA6 copolymer (PADA) with low melting point and good anti-dripping performance was designed via a facile bulk copolymerization method. Azobenzene (self-crosslinked unit) as the functional segment was introduced into the PA6 backbone under the favorable assistance of ethylene glycol (EG, a chain-linker). Specifically, a satisfactory reduction of approximately 50 °C in melting point was achieved for PADAs compared with PA6 due to the destroyed regularity of the molecular chain. Meanwhile, the PADAs reached an LOI value of 28.2% with totally suppressed melt-dripping behavior, and the formed crosslinked network that originated from the synergistic effect of azobenzene and EG during combustion was proved to be an essential factor for the improved anti-dripping performance. The proposed synthesis method overcomes the difficulty of the requirement for the absolutely equivalent molar ratio of amine to carboxyl groups in PA6 copolymerization, and thus appeals to a broader focus on developing traditional PA6. Graphical Abstract: ga1 Highlights: PA6 containing azobenzene groups was synthesized under the assistance of ethylene glycol. A satisfactory reduction about 50 °C in melting point ( T m ) was achieved for PADAs. PADAs exhibited totally suppressed melt-dripping behavior.